Heterogeneous regional university funding and firm innovation: An empirical analysis of the German excellence initiative - Bastian Krieger (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2023)
This paper estimates the effect of heterogeneous university funding stemming from the German Excellence Initiative on a regional firm's probability to innovate by using a multi-valued two-way fixed effects difference-in-differences model. The estimations show that funding an additional Excellence Cluster focused on internationally competitive research within a labor market region increases a regional firm's probability to innovate between 0.3 and 0.9 percentage points. This effect is driven by firms within labor market regions receiving a high number of Excellence Clusters. There is no statistically significant effect for receiving a low number of Excellence Clusters. Moreover, we find no consistent statistically significant effect of funding Graduate Schools concentrating on training scientists nor of funding University Strategies promoting the overall long-term plan of a university.
Keywords: O32; O33; O38; 330; University funding; Firm innovation; Knowledge transfer